Dinâmica e eficácia de diferentes herbicidas pré emergentes na cultura do milho - Zamboni, Leonardo Brandelero (2024)
The commercialization and use of corn plays a very important role in terms of global production, being the most cultivated cereal in the world, having great value in the Brazilian economy, making Brazil the third largest producer and the largest exporter of this cereal in the world. Therefore, to maintain high productivity, it is necessary to use techniques that avoid possible losses. The use of herbicides can suppress several weeds that cause financial damage to producers with reduced yield. Chemical control is widely used to combat weeds that compete with the crop and hinder its growth. Based on this knowledge and aiming to determine which preemergent herbicides are most effective in controlling weeds and reducing disturbances in weed competition with corn, the experiment was carried out on the experimental farm of the UTFPR-Dois Vizinhos Paraná campus. , in the 2022/2023 harvest with the AG 8701 PRO 3 hybrid in an experimental area of 288 m2, with 24 plots adopted. The experimental design used was Randomized Blocks (DBC), with four blocks and six treatments. Products (6 treatments) with the active ingredient of Isoxaflutol + Thiencarbazone-methyl, Cletodim + Aromatic Naphtha, Atrazine and SMetalochlor were used, which were applied in the plant applique modality. For comparison within treatment, the clean control (TL) and dirty control (TS) were also adopted. Subsequently, the collected data were statistically analyzed using the ScotKnott test. With the data obtained, it is observed that the doses of S-Metalochlor showed a significantly lower performance, with averages statistically equal to or lower than those of the dirty control, indicating an ineffectiveness in its use as a preemergent in this study. On the other hand, the plots treated with Isoxuflatol+Methyl Thiencarbazone and Atrazine were satisfactory in controlling weeds in the four evaluations carried out up to 28 days after emergence (DAE). Except for measurements up to 28 DAE of dry matter and corn plant height, the plots treated with Isoxaflutole showed superior performance, with values statistically better than or equal to those of the clean control. This study showed positive results, observing interference from herbicides together with weeds that act directly on the seed bank, aiming for greater productivity, with emphasis on the use of the herbicide isoxaflutole + Thiencarbazone-methyl, which stood out in most evaluations.